Coal-based hard carbon negative electrode material, preparation method thereof and sodium ion battery
Through the esterification cross-linking treatment of modified coal powder and high amylose, a coal-based hard carbon negative electrode material with high specific capacity and first Coulomb efficiency was prepared, which solved the problem of the low reversible capacity and first Coulomb efficiency of existing materials in sodium ion batteries. Low problem.
Patent Information
- Application Number
- CN202411608309.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing coal-based hard carbon anode material has problems such as high ash content, low reversible capacity, and low Coulomb efficiency in sodium ion batteries, which affects the mass energy density of the battery.
By synchronous purification and pre-oxidation treatment of coal powder and mixed acid, the modified coal powder and high amylose are mixed in solid phase and esterified and cross-linked, and the mass ratio is controlled to be 6-9:1-4, and esterification, pre-carbonization and carbonization are carried out. The coal-based hard carbon negative electrode material with an expanded layer spacing, an increased proportion of pseudographite phase and a reduced specific surface area was prepared.
The specific capacity and first Coulomb efficiency of coal-based hard carbon negative electrode materials are improved, the carbon yield is improved, and the structural stability and reversibility of the material are enhanced.
Smart Images

Figure BDA0005130252610000131 
Figure BDA0005130252610000132 
Figure HDA0005130252620000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery material preparation, and in particular to a coal-based hard carbon negative electrode material, a preparation method thereof, and a sodium ion battery. Background Art
[0002] In application scenarios where the requirements for volume energy density are not very high, such as battery swap stations, low-speed four-wheel electric vehicles, two-wheel electric vehicles, etc., sodium-ion batteries are expected to become a powerful supplement to lithium-ion batteries to cope with the risks of relatively scarce lithium resources and drastic fluctuations in the lithium battery market. As one of the most important components of sodium batteries, the negative electrode has developed carbon-based, metal oxide, alloy and organic materials. From the perspectives of resources, cost, and industrialization, carbon-based materials are still attracting much attention. Among them, hard carbon has a large interlayer spacing and long-range disordered structure, which is suitable for reversible storage and transmission of sodium ions, and the preparation process is relatively simple. It has recently become a research hotspot in the academic community, and various related companies have also laid out the research and development and production line construction of hard carbon.
[0003] At present, the mainstream precursors of hard carbon include biomass, high molecular polymer, asphalt, coal, etc. Biomass hard carbon is affected by seasons and regions, and needs to compete with the traditional activated carbon industry for market share. The price of high molecular polymer is relatively expensive, and asphalt tends to form soft carbon during high temperature carbonization. In terms of batch stability and cost of comprehensive raw materials, coal-based hard carbon has a higher competitive advantage.
[0004] Coal can be divided into lignite, sub-bituminous coal, bituminous coal and anthracite according to its degree of metamorphism. As the coal rank increases, the proportion of polycyclic aromatic hydrocarbons in the coal increases, the number of oxygen-containing functional groups such as carboxyl and hydroxyl groups on the surface and edge decreases, and the prepared hard carbon has a smaller interlayer spacing and a larger crystallite size, which is not conducive to sodium storage. Although there are many choices for raw materials for coal-based hard carbon, most products face problems such as high ash content, low reversible capacity, and low first coulombic efficiency. Improving the specific capacity and first efficiency of coal-based hard carbon is of great significance to improving the mass energy density of the whole battery. Summary of the invention
[0005] The purpose of the present invention is to provide a coal-based hard carbon negative electrode material and a method for preparing the same and a sodium ion battery. The coal-based hard carbon prepared by the preparation method of the present invention has an enlarged interlayer spacing, an increased pseudographite phase ratio and a reduced specific surface area, and when used as a negative electrode material for a sodium ion battery, it exhibits a higher specific capacity and first coulombic efficiency, and can improve the carbon yield.
[0006] To achieve the above object, the first aspect of the present invention provides a method for preparing a coal-based hard carbon negative electrode material, comprising the steps of:
[0007] (I) performing simultaneous purification and pre-oxidation treatment on coal powder and mixed acid in a solvent to obtain modified coal powder, wherein the mixed acid includes hydrochloric acid, hydrofluoric acid and nitric acid;
[0008] (II) solid-phase mixing the modified coal powder and starch to obtain a first precursor, wherein the amylose content in the starch is 50% or more, and the mass ratio of the modified coal powder to the starch is 6-9:1-4;
[0009] (III) sequentially esterifying and pre-carbonizing the first precursor to obtain a second precursor;
[0010] (IV) Carbonizing the second precursor to obtain a coal-based hard carbon negative electrode material.
[0011] Compared with the prior art, the present invention first treats the coal powder in a mixed acid, which includes hydrochloric acid, hydrofluoric acid and nitric acid. The mixed acid can effectively remove impurities contained in the coal powder, and the coal powder can also be modified to increase the carboxyl functional groups on its surface. The modified coal powder is then mixed with starch having a straight chain starch content of more than 50% and above in a solid phase and then esterified, and the mass ratio of the two is controlled to be 6-9:1-4. Under this condition, the carboxyl groups contained on the surface of the modified coal powder and the hydroxyl groups contained in the starch are esterified and cross-linked, so that the starch and the coal powder are closely combined, and the structure is stabilized, so that the weight loss rate of the composite material is lower than the linear superposition weight loss rate of the two, and the carbon yield is improved. In addition, since the coal powder is rich in aromatic structure, the carbon microcrystals are easy to be long-range ordered during the carbonization process. After the ester functional group is introduced through the esterification reaction, its long-range ordered growth can be inhibited, and the carbon layer spacing is expanded, and the proportion of pseudographite phase in the prepared hard carbon is increased, which helps to improve its reversible capacity. At the same time, the pores and defects on the surface of the material are reduced after esterification and cross-linking, and the specific surface area is reduced, so the first coulombic efficiency is increased.
[0012] In some embodiments, the particle size D of the coal powder is v 50 is 2μm~10μm.
[0013] In some embodiments, the concentration of hydrochloric acid is 36 wt.% to 38 wt.%, the concentration of hydrofluoric acid is ≥ 40 wt.%, and the concentration of nitric acid is ≥ 20 wt.%.
[0014] In some embodiments, the solvent is selected from water, and the water is tap water or purified water.
[0015] In some embodiments, the mass ratio of coal powder, hydrochloric acid, hydrofluoric acid, nitric acid and solvent is 1:0.5-1.5:0.1-0.5:0.1-0.5:1.0-5.0.
[0016] In some embodiments, the temperature of the simultaneous purification pre-oxidation treatment is 50° C. to 90° C., and the time is 4 h to 24 h.
[0017] In some embodiments, the esterification and pre-carbonization are performed in an inert atmosphere selected from at least one of nitrogen, helium and argon.
[0018] In some embodiments, the esterification temperature is 150° C. to 350° C., the esterification heating rate is 1° C. / min to 10° C. / min, and the insulation time is 1 h to 10 h.
[0019] In some embodiments, the pre-carbonization temperature is 450° C. to 900° C., the heating rate is 1° C. / min to 10° C. / min, and the holding time is 1 h to 10 h.
[0020] In some embodiments, the carbonization is performed in an inert atmosphere selected from at least one of nitrogen, helium, and argon.
[0021] In some embodiments, the carbonization temperature is 1100° C. to 1600° C., the heating rate is 1° C. / min to 10° C. / min, and the holding time is 1 h to 10 h.
[0022] In some embodiments, the coal powder is obtained by coarsely crushing, drying and pulverizing the raw coal.
[0023] In some embodiments, the raw coal is selected from at least one of lignite, sub-bituminous coal, bituminous coal, and anthracite.
[0024] In some embodiments, the particle size D of the raw coal is v 100 is 0.1cm~1.0cm.
[0025] In some embodiments, the raw coal is dried at a temperature of 50° C. to 100° C., and the drying time is 12 h to 72 h.
[0026] In some embodiments, the raw coal is pulverized by at least one of air flow milling, roller milling and mechanical milling.
[0027] In some embodiments, after the simultaneous purification and pre-oxidation treatment, the purified pre-oxidation material is filtered once, washed with water, filtered twice until the filtrate is neutral, and then dried.
[0028] In some embodiments, the primary filtration and the secondary filtration are each independently selected from negative pressure filtration, positive pressure filtration, or centrifugal filtration.
[0029] In some embodiments, the water washing temperature is 20°C to 90°C, and the washing time is 4h to 24h.
[0030] In some embodiments, in the water wash, the mass ratio of the purified pre-oxidized material to water is 1:1-50.
[0031] In some embodiments, in water washing, the water is tap water or purified water.
[0032] In some embodiments, the drying temperature is 50° C. to 100° C., and the drying time is 12 h to 72 h.
[0033] In some embodiments, screening and demagnetization are sequentially included after carbonization.
[0034] In some embodiments, the mesh size of the sieve used for sieving is 300-500 mesh.
[0035] A second aspect of the present invention provides a coal-based hard carbon negative electrode material, which is prepared by the aforementioned preparation method.
[0036] A third aspect of the present invention provides a sodium ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material is the aforementioned coal-based hard carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 These are the thermogravimetric curves of the first precursor in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2.
[0038] Figure 2 The XRD spectra of the coal-based hard carbon negative electrode materials prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2 are shown.
[0039] Figure 3 This is the peak fitting curve of 002 peak in the XRD spectrum of the coal-based hard carbon negative electrode material prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0040] The present invention provides a sodium ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material is a coal-based hard carbon negative electrode material of the present invention. The coal-based hard carbon negative electrode material of the present invention can be used alone or mixed with other negative electrode materials (such as expanded graphite, graphite intercalation compounds and soft carbon, etc.). The method for preparing the coal-based hard carbon negative electrode material of the present invention comprises the steps of:
[0041] (I) subjecting coal powder and mixed acid to simultaneous purification and pre-oxidation treatment in a solvent to obtain modified coal powder;
[0042] (II) solid-phase mixing the modified coal powder and starch to obtain a first precursor;
[0043] (III) sequentially esterifying and pre-carbonizing the first precursor to obtain a second precursor;
[0044] (IV) Carbonizing the second precursor to obtain a coal-based hard carbon negative electrode material.
[0045] In step (I), the mixed acid includes hydrochloric acid, hydrofluoric acid and nitric acid, wherein the concentration of hydrochloric acid is 36wt.% to 38wt.%, the concentration of hydrofluoric acid is ≥40wt.%, and the concentration of nitric acid is ≥20wt.%. The coal powder is placed in the mixed acid including hydrochloric acid, hydrofluoric acid and nitric acid for purification and pre-oxidation treatment, which can effectively remove impurities in the coal powder, and at the same time, the strong oxidizing effect of the mixed acid is used to modify the coal powder, and carboxyl functional groups can be formed on its surface. The mass ratio of coal powder, hydrochloric acid, hydrofluoric acid, nitric acid and solvent is 1.0: 0.5 to 1.5: 0.1 to 0.5: 0.1 to 0.5: 1.0 to 5.0. In some technical schemes, the mass ratio of coal powder, hydrochloric acid, hydrofluoric acid, nitric acid and solvent is 1.0:0.6~1.2:0.1~0.4:0.1~0.3:1.0~4.5; in some technical schemes, the mass ratio of coal powder, hydrochloric acid, hydrofluoric acid, nitric acid and solvent is 1.0:0.5~0.8:0.1~0.3:0.1~0.2:1.2~2.8; in some technical schemes, the mass ratio of coal powder, hydrochloric acid, hydrofluoric acid, nitric acid and solvent is 1.0:0.6:0.2:0.2:1.5. As an example, the mass ratio of coal powder, hydrochloric acid, hydrofluoric acid, nitric acid and solvent can be, but is not limited to, 1.0:0.5:0.1:0.1:1.2, 1.0:0.5:0.2:0.1:1.2, 1.0:0.5:0.1:0.2:1.2, 1.0:0.5:0.3:0.2:1.2, 1.0:0.5:0.1:0.2:1.4, 1.0:0.5:0.1:0.2: 1.8、1.0:0.5:0.1:0.2:2.0、1.0:0.6:0.1:0.1:1.2、1.0:0.6:0.2:0.1:1.2、1.0:0.6:0.1:0.2:1.2、1.0:0.6:0.3:0.2:1.2、1.0:0.6:0.1:0.2:1.4、1.0:0.6:0.1:0.2:1.8、1.0: 0.6:0.1:0.2:2.0、1.0:0.8:0.1:0.1:1.2、1.0:0.8:0.2:0.1:1.2、1.0:0.8:0.1:0.2:1.2、1.0:0.8:0.3:0.2:1.2、1.0:0.8:0.1:0.2:1.4、1.0:0.8:0.1:0.2:1.8、1.0:0.8:0.1: 0.2:2.0, 1.0:1.0:0.1:0.1:1.2, 1.0:1.0:0.2:0.1:1.2, 1.0:1.0:0.1:0.2:1.2, 1.0:1.0:0.3:0.2:1.2, 1.0:1.0:0.1:0.2:1.4, 1.0:1.0:0.1:0.2:1.8, 1.0:1.0:0.1:0.2:2.0. The solvent can be selected from water, and the water is tap water or purified water. The particle size D of the coal powderv 50 is 2 μm to 10 μm. As an example, the particle size D of the coal powder is v 50 can be, but is not limited to, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm. Coal powder is obtained by coarsely breaking, drying, and pulverizing raw coal.
[0046] The raw coal is selected from at least one of lignite, sub-bituminous coal, bituminous coal and anthracite. In some technical solutions, the raw coal is selected from bituminous coal. The particle size D of the raw coal is v 100 is 0.1cm~1.0cm. As an example, the particle size D of the raw coal is roughly crushed. v 100 may be, but is not limited to, 0.1 cm, 0.2 cm, 0.3 cm, 0.4 cm, 0.5 cm, 0.6 cm, 0.7 cm, 0.8 cm, 0.9 cm, and 1.0 cm. The temperature of raw coal drying is 50°C to 100°C. In some technical solutions, the temperature of raw coal drying is 55°C to 95°C. In some technical solutions, the temperature of raw coal drying is 80°C to 90°C. In some technical solutions, the temperature of raw coal drying is 85°C. As an example, the temperature of raw coal drying may be, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, 90°C, 92°C, 94°C, 95°C, 98°C, and 100°C. The time for drying the raw coal is 12h to 72h. In some technical solutions, the time for drying the raw coal is 18h to 48h. In some technical solutions, the time for drying the raw coal is 24h. As an example, the time for drying the raw coal can be, but is not limited to, 12h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 36h, 48h, 60h, and 72h. The method for crushing the raw coal includes at least one of air flow mill, roller mill, and mechanical mill.
[0047] The temperature of the synchronous purification pre-oxidation treatment is 50°C to 90°C. In some technical solutions, the temperature of the synchronous purification pre-oxidation treatment is 55°C to 85°C. In some technical solutions, the temperature of the synchronous purification pre-oxidation treatment is 58°C to 82°C. In some technical solutions, the temperature of the synchronous purification pre-oxidation treatment is 70°C. As an example, the temperature of the synchronous purification pre-oxidation treatment can be, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, and 90°C. The time of the synchronous purification pre-oxidation treatment is 4h to 24h. In some technical solutions, the time of the synchronous purification pre-oxidation treatment is 5h to 18h. In some technical solutions, the time of the synchronous purification pre-oxidation treatment is 6h. As an example, the time of the synchronous purification pre-oxidation treatment can be, but is not limited to, 4h, 5h, 6h, 7h, 8h, 12h, 16h, 20h, and 24h.
[0048] After the simultaneous purification pre-oxidation treatment, the purified pre-oxidation material is filtered once, washed with water, and filtered twice until the filtrate is neutral and then dried. The primary filtration and the secondary filtration are each independently selected from negative pressure filtration, positive pressure filtration or centrifugal filtration. In the water washing, the mass ratio of the purified pre-oxidation material to water is 1:1 to 50. In some technical schemes, the mass ratio of the purified pre-oxidation material to water is 1:2 to 20. In some technical schemes, the mass ratio of the purified pre-oxidation material to water is 1:4. As an example, the mass ratio of the purified pre-oxidation material to water can be, but is not limited to, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:10, 1:15, 1:20, 1:25, 1:30. The water is tap water or purified water. The water washing temperature is 20°C to 90°C. In some technical solutions, the water washing temperature is 30°C to 85°C. In some technical solutions, the water washing temperature is 58°C to 80°C. In some technical solutions, the water washing temperature is 70°C. As an example, the water washing temperature can be, but is not limited to, 20°C, 30°C, 40°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C. The water washing time is 4h to 24h. In some technical solutions, the water washing time is 6h. As an example, the water washing time can be, but is not limited to, 4h, 5h, 6h, 7h, 8h, 12h, 16h, 20h, 24h.
[0049] The drying can be specifically carried out in an oven. The drying temperature is 50°C to 100°C. In some technical solutions, the drying temperature is 55°C to 95°C. In some technical solutions, the drying temperature is 80°C to 90°C. In some technical solutions, the drying temperature is 85°C. As an example, the drying temperature can be, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, 90°C, 92°C, 94°C, 95°C, 98°C, and 100°C. The drying time is 12h to 72h. In some technical solutions, the drying time is 18h to 48h. In some technical solutions, the drying time is 24h. As an example, the drying time can be but is not limited to 12h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 36h, 48h, 60h, and 72h.
[0050] In step (II), the mass ratio of modified coal powder to starch is 6 to 9:1 to 4. As an example, the mass ratio of modified coal powder to starch can be, but is not limited to, 6:1, 6:2, 6:3, 6:4, 7:1, 7:2, 7:3, 7:4, 8:1, 8:2, 8:3, 8:4, 9:1, 9:2, 9:3, 9:4. Solid-phase mixing of modified coal powder and starch at a mass ratio of 6 to 9:1 to 4 can make the starch and coal powder mixed more evenly, and in the subsequent esterification process, the starch and the modified coal powder can be better esterified and cross-linked, thereby obtaining a coal-based hard carbon negative electrode material with a higher specific capacity and first coulomb efficiency. Solid-phase mixing avoids the step of drying after liquid-phase mixing, and the process is simpler and improves the utilization rate of raw materials. The content of amylose in starch is 50% or more, that is, the starch used in the present invention is high-amylose starch.
[0051] In step (III), esterification and pre-carbonization can be carried out in an inert atmosphere, and the inert atmosphere can be selected from at least one of nitrogen, argon and helium. The temperature of esterification is 150°C to 350°C. In some technical schemes, the temperature of esterification is 165°C to 325°C. In some technical schemes, the temperature of esterification is 215°C to 295°C. In some technical schemes, the temperature of esterification is 270°C to 285°C. In some technical schemes, the temperature of esterification is 280°C. As an example, the temperature of esterification can be, but is not limited to, 150°C, 180°C, 200°C, 220°C, 240°C, 250°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C. The heating rate of esterification is 1°C / min to 10°C / min. In some technical solutions, the heating rate of esterification is 3°C / min to 8°C / min. In some technical solutions, the heating rate of esterification is 5°C / min. As an example, the heating rate of esterification can be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min. The insulation time of esterification is 1h to 10h. In some technical solutions, the insulation time of esterification is 2h. As an example, the insulation time of esterification can be, but is not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h. Under the above conditions, the carboxyl groups on the surface of the modified coal powder react with the hydroxyl groups in the starch to react with the starch through an ester bond, thereby improving the structural stability of the material, so that the weight loss rate of the composite material is lower than the linear superposition weight loss rate of the two, and the carbon yield is improved. In addition, since the coal powder is rich in aromatic structures, the carbon microcrystals are prone to long-range order during the carbonization process. Through the esterification reaction, ester functional groups are introduced, which is conducive to inhibiting the long-range orderly growth of carbon microcrystals during the carbonization of the coal powder, expanding the distance between carbon layers, and increasing the proportion of pseudographite phase in the prepared hard carbon. Esterification cross-linking helps to reduce the pores and defects on the surface of the material, so that it has a reduced specific surface area, thereby improving the reversible capacity and the first coulomb efficiency.
[0052] The temperature of pre-carbonization is 450°C to 900°C. In some technical solutions, the temperature of pre-carbonization is 550°C. As an example, the temperature of pre-carbonization can be, but is not limited to, 450°C, 460°C, 480°C, 500°C, 515°C, 525°C, 535°C, 545°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C. The heating rate of pre-carbonization is 1°C / min to 10°C / min. In some technical solutions, the heating rate of pre-carbonization is 3°C / min to 7°C / min. In some technical solutions, the heating rate of pre-carbonization is 5°C / min. As an example, the heating rate of pre-carbonization can be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. The insulation time of pre-carbonization is 1h to 10h. In some technical solutions, the insulation time of pre-carbonization is 2h. As an example, the insulation time of pre-carbonization can be, but is not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h.
[0053] In step (IV), the carbonization temperature is 1100°C to 1600°C. In some technical solutions, the carbonization temperature is 1350°C to 1480°C. In some technical solutions, the carbonization temperature is 1380°C to 1450°C. In some technical solutions, the carbonization temperature is 1400°C. As an example, the carbonization temperature can be, but is not limited to, 1100°C, 1200°C, 1300°C, 1320°C, 1340°C, 1360°C, 1380°C, 1400°C, 1410°C, 1420°C, 1440°C, 1460°C, 1480°C, 1500°C, 1600°C. The heating rate of carbonization is 1°C / min to 10°C / min. In some technical solutions, the heating rate of carbonization is 4°C / min to 8°C / min. In some technical solutions, the heating rate of carbonization is 5°C / min. As an example, the heating rate of carbonization can be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. The insulation time of carbonization is 1h to 10h. In some technical schemes, the insulation time of carbonization is 2h. As an example, the insulation time of carbonization can be, but is not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h. Carbonization can be carried out in an inert atmosphere, and the inert atmosphere can be selected from at least one of nitrogen, argon and helium.
[0054] After carbonization, the process also includes screening and demagnetization to obtain the coal-based hard carbon negative electrode material. The mesh size of the sieve used for screening is 300-500 mesh. As an example, the mesh size of the sieve used for screening can be, but is not limited to, 325 mesh, 360 mesh, 400 mesh, and 500 mesh.
[0055] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0056] Example 1
[0057] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the steps of:
[0058] (I) Crushing bituminous coal to a particle size of D v 100 is 0.5 cm, and is placed in an oven at 75 ° C for 30 h. The dried bituminous coal is crushed to obtain a particle size D v 50 is 5 μm coal powder; add coal powder, 36wt.% hydrochloric acid, 40wt.% hydrofluoric acid, 20wt.% nitric acid and water in a mass ratio of 1:0.6:0.2:0.2:1.4 into a reactor, and react at 50°C for 8h, and filter once after cooling to room temperature to obtain a purified pre-oxidized material; then add it and water in a mass ratio of 1:2 into a reactor, react at 90°C for 4h, and filter twice after cooling to room temperature, and repeat until the pH of the filtrate is 7; place the washed purified pre-oxidized material in an oven at 95°C and dry for 18h to obtain modified coal powder;
[0059] (II) solid-phase mixing the modified coal powder and starch at a mass ratio of 9:1 to obtain a first precursor, wherein the amylose content in the starch is 50% or more;
[0060] (III) in a nitrogen atmosphere, heating the first precursor to 260° C. at a rate of 9° C. / min and keeping the temperature for 3 h for esterification, then heating to 500° C. at a rate of 9° C. / min and keeping the temperature for 1 h for pre-carbonization, and naturally cooling to room temperature to obtain a second precursor;
[0061] (IV) In a nitrogen atmosphere, the second precursor is heated to 1300° C. at a rate of 9° C. / min and maintained at this temperature for 3 h, and then naturally cooled to room temperature to obtain a carbonized material; the carbonized material is sieved through a 325-mesh sieve and demagnetized to obtain a coal-based hard carbon negative electrode material.
[0062] Example 2
[0063] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the steps of:
[0064] (I) Crushing bituminous coal to a particle size of D v 100 is 0.6 cm, and is placed in an oven at 85°C for 24 h. The dried bituminous coal is crushed to obtain a particle size D v 50 is 6 μm coal powder; add coal powder, 36wt.% hydrochloric acid, 40wt.% hydrofluoric acid, 20wt.% nitric acid and water in a mass ratio of 1:0.5:0.3:0.1:1.5 into a reactor, and react at 70°C for 6 hours, and filter once after cooling to room temperature to obtain a purified pre-oxidized material; then add it and water in a mass ratio of 1:4 into a reactor, react at 70°C for 6 hours, and filter twice after cooling to room temperature, and repeat until the pH of the filtrate is 7; place the washed purified pre-oxidized material in an oven at 85°C and dry for 24 hours to obtain modified coal powder;
[0065] (II) solid-phase mixing the modified coal powder and starch at a mass ratio of 8:2 to obtain a first precursor, wherein the content of amylose in the starch is 50% or more;
[0066] (III) in a nitrogen atmosphere, heating the first precursor to 280° C. at a rate of 5° C. / min and keeping the temperature for 2 h for esterification, then heating to 550° C. at a rate of 5° C. / min and keeping the temperature for 2 h for pre-carbonization, and then naturally cooling to room temperature to obtain a second precursor;
[0067] (IV) In a nitrogen atmosphere, the second precursor is heated to 1400° C. at a rate of 5° C. / min and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a carbonized material; the carbonized material is sieved through a 325-mesh sieve and demagnetized to obtain a coal-based hard carbon negative electrode material.
[0068] Example 3
[0069] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the steps of:
[0070] (I) Crushing bituminous coal to a particle size of D v 100 is 0.7 cm, and is placed in an oven at 80 ° C for 21 h. The dried bituminous coal is crushed to obtain a particle size D v 50 is 7μm coal powder; add coal powder, 36wt.% hydrochloric acid, 40wt.% hydrofluoric acid, 20wt.% nitric acid and water in a mass ratio of 1:0.8:0.2:0.2:1.2 into a reactor, and react at 60°C for 5h, and filter once after cooling to room temperature to obtain a purified pre-oxidized material; then add it and water in a mass ratio of 1:3 into a reactor, react at 60°C for 5h, and filter twice after cooling to room temperature, and repeat until the pH of the filtrate is 7; place the washed purified pre-oxidized material in an oven at 80°C and dry for 21h to obtain modified coal powder;
[0071] (II) solid-phase mixing the modified coal powder and starch in a mass ratio of 7:3 to obtain a first precursor, wherein the amylose content in the starch is 50% or more;
[0072] (III) in a nitrogen atmosphere, heating the first precursor to 270° C. at a rate of 3° C. / min and keeping the temperature for 1.5 h for esterification, then heating to 520° C. at a rate of 3° C. / min and keeping the temperature for 2.5 h for pre-carbonization, and then naturally cooling to room temperature to obtain a second precursor;
[0073] (IV) In a nitrogen atmosphere, the second precursor is heated to 1350° C. at a rate of 3° C. / min and maintained at this temperature for 1.5 h, and then naturally cooled to room temperature to obtain a carbonized material; the carbonized material is sieved through a 325-mesh sieve and demagnetized to obtain a coal-based hard carbon negative electrode material.
[0074] Example 4
[0075] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the steps of:
[0076] (I) Crushing bituminous coal to a particle size of D v 100 is 1.0 cm, and is placed in an oven at 95°C for 18 h. The dried bituminous coal is crushed to obtain a particle size D v 50 is 10 μm coal powder; add coal powder, 38wt.% hydrochloric acid, 45wt.% hydrofluoric acid, 24wt.% nitric acid and water in a mass ratio of 1:1:0.1:0.3:1 into a reactor, and react at 80°C for 4 hours, and filter once after cooling to room temperature to obtain a purified pre-oxidized material; then add it and water in a mass ratio of 1:6 into a reactor, react at 50°C for 8 hours, and filter twice after cooling to room temperature, and repeat until the pH of the filtrate is 7; place the washed purified pre-oxidized material in an oven at 75°C and dry for 30 hours to obtain modified coal powder;
[0077] (II) solid-phase mixing the modified coal powder and starch in a mass ratio of 6:4 to obtain a first precursor, wherein the amylose content in the starch is 50% or more;
[0078] (III) in a nitrogen atmosphere, heating the first precursor to 300° C. at a rate of 1° C. / min and keeping the temperature for 1 h for esterification, then heating to 600° C. at a rate of 1° C. / min and keeping the temperature for 3 h for pre-carbonization, and then naturally cooling to room temperature to obtain a second precursor;
[0079] (IV) In a nitrogen atmosphere, the second precursor is heated to 1500° C. at a rate of 1° C. / min and maintained at this temperature for 1 h, and then naturally cooled to room temperature to obtain a carbonized material; the carbonized material is sieved through a 325-mesh sieve and demagnetized to obtain a coal-based hard carbon negative electrode material.
[0080] Figure 3 The 002 peak fitting curve in the XRD spectrum of the coal-based hard carbon prepared in this example is shown.
[0081] Comparative Example 1
[0082] This comparative example is a method for preparing a coal-based hard carbon negative electrode material, comprising the steps of:
[0083] (I) Crushing bituminous coal to a particle size of D v 100 is 0.6 cm, and is placed in an oven at 85°C for 24 h. The dried bituminous coal is crushed to obtain a particle size D v 50 is 6 μm coal powder; add coal powder, 36wt.% hydrochloric acid, 40wt.% hydrofluoric acid, 20wt.% nitric acid and water in a mass ratio of 1:0.5:0.3:0.1:1.5 into a reactor, and react at 70°C for 6 hours, and filter once after cooling to room temperature to obtain a purified pre-oxidized material; then add it and water in a mass ratio of 1:4 into a reactor, react at 70°C for 6 hours, and filter twice after cooling to room temperature, and repeat until the pH of the filtrate is 7; place the washed purified pre-oxidized material in an oven at 85°C and dry for 24 hours to obtain modified coal powder;
[0084] (II) In a nitrogen atmosphere, the modified coal powder (i.e., the first precursor) was heated to 280°C at a rate of 5°C / min and kept at this temperature for 2 h, then heated to 550°C at a rate of 5°C / min and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a second precursor;
[0085] (III) In a nitrogen atmosphere, the second precursor is heated to 1400° C. at a rate of 5° C. / min and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a carbonized material; the carbonized material is sieved through a 325-mesh sieve and demagnetized to obtain a coal-based hard carbon negative electrode material.
[0086] Comparative Example 2
[0087] This comparative example is a method for preparing a coal-based hard carbon negative electrode material, comprising the steps of:
[0088] (I) In a nitrogen atmosphere, starch (i.e., the first precursor) is heated to 280° C. at a rate of 5° C. / min and kept at this temperature for 2 h, then heated to 550° C. at a rate of 5° C. / min and kept at this temperature for 2 h, and naturally cooled to room temperature to obtain a second precursor, wherein the amylose content in the starch is 50% or more;
[0089] (II) In a nitrogen atmosphere, the second precursor is heated to 1400° C. at a rate of 5° C. / min and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a carbonized material; the carbonized material is sieved through a 325-mesh sieve and demagnetized to obtain a coal-based hard carbon negative electrode material.
[0090] The physical and chemical properties of the coal-based hard carbon negative electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were tested, and they were made into half-cells for electrochemical performance testing. The half-cell preparation process and test conditions are as follows, and the test and analysis results are shown in Tables 1 and 2.
[0091] Thermogravimetric:
[0092] The thermal weight loss of the material was determined according to the national standard GB / T 27761-2011 “Test method for weight loss and residual amount by thermogravimetric analyzer”.
[0093] Specific surface area:
[0094] The nitrogen adsorption / desorption isotherms of the materials were obtained by Micromeritics ASAP 2460 analyzer, and their specific surface areas were calculated by the BET method.
[0095] Preparation of half-cell:
[0096] The active material and the binder carboxymethyl cellulose (CMC) were uniformly dispersed in deionized water at a mass ratio of 95:5 to obtain a slurry, which was then coated on a copper foil. After being dried in a vacuum oven at 120°C for 12 hours, the slurry was cut into discs with a diameter of 1 cm. The surface density of the active material loaded on the discs was 0.8-1.0 mg / cm 2 In a glove box with argon atmosphere (H 2 O<0.1ppm, O 2 <0.1ppm), with metallic sodium as the counter electrode, 1MNaClO 4 Ethylene carbonate (EC) and diethyl carbonate (DEC) dissolved in a volume ratio of 1:1 and 5% fluoroethylene carbonate (FEC) were used as the electrolyte to assemble CR2032 button cells.
[0097] Specific capacity:
[0098] The charge and discharge tests were carried out in the potential range of 0 to 2 V, and the charge capacity (sodium removal) was taken as the reversible capacity.
[0099] First Coulombic efficiency:
[0100] The ratio of the charge capacity (sodium removal) to the discharge capacity (sodium insertion) during the first cycle.
[0101] Table 1 Physical and chemical test data of Examples 1 to 4 and Comparative Examples 1 to 2
[0102]
[0103] Table 2 XRD test and peak fitting data of coal-based hard carbon prepared in Examples 1 to 4 and Comparative Examples 1 to 2
[0104]
[0105] It can be seen from Table 1 that the 800°C weight loss rate of the bituminous coal in Comparative Example 1 is 36.85%, while the 800°C weight loss rate of the starch in Comparative Example 2 is 88.93%. The higher weight loss rate means a lower carbon yield, which is not conducive to cost control. The weight loss rate of the mixed materials in Examples 1 to 4 is between the two and is lower than the linear superposition weight loss rate of each item. This is mainly because bituminous coal has abundant carboxyl groups and starch is rich in hydroxyl groups. Chemical crosslinking occurs between the two during the esterification stage, which stabilizes the structure. Table 2 shows the XRD test and peak fitting data of the hard carbon prepared in Examples 1 to 4 and Comparative Examples 1 to 2. The d of Comparative Example 1 002 Small, not conducive to the reversible extraction / embedding of sodium ions, comparative example 2 d 002 The larger the specific capacity in Table 1, the greater the specific capacity. Examples 1 to 4 have an enlarged d 002 , which helps to improve its sodium storage performance. Further peak fitting was performed on the 002 peak of each XRD test. The hard carbon derived from bituminous coal in Example 1 consisted of pseudographite phase. and graphite-like phase The former accounts for a smaller proportion; while the hard carbon prepared by starch in Comparative Example 2 consists of amorphous domains and pseudographite phase, and the latter accounts for up to 72.52%. The proportion of pseudographite phase in Examples 1 to 4 is significantly increased compared with Comparative Example 1. In Table 1, the specific surface areas of Examples 1 to 4 are all reduced compared with Comparative Example 1, which reduces the interface contact between the material and the electrolyte, thereby increasing the first coulomb efficiency.
[0106] Figure 1 The thermogravimetric curves of the precursors in Examples 1 to 4 and Comparative Examples 1 to 2. As can be seen from the figure, the weight loss of all curves at around 100°C corresponds to the removal of adsorbed water, the weight loss of Comparative Example 1 at 257.7°C is due to the release of small molecules in coal, and the weight of Comparative Example 2 drops sharply at 312.1°C, indicating that the starch is pyrolyzed to form small molecules that volatilize. Clarifying the thermal decomposition range of each species can help determine the approximate temperature range of esterification and cross-linking. At the final temperature of 800°C, the weight loss rate in Comparative Example 1 is 36.85%, the weight loss rate in Comparative Example 2 is 88.93%, and the weight loss rate in Examples 1 to 4 is between that of coal and starch, and each weight loss rate is lower than the linear superposition weight loss rate of the two, indicating that in the process of gradually increasing the temperature, chemical cross-linking occurs between the coal and the high-amylose starch to stabilize the structure, so that the material has enhanced thermal stability, which is beneficial to improving the carbon yield.
[0107] Figure 2 The XRD spectra of the hard carbons prepared in Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Figure 2. 002 Only This is mainly because coal is rich in aromatic ring structures and is easy to accumulate densely during the carbonization process. 002 for The 002 peak is broader than that in Comparative Example 1, indicating that the microstructure of starch-derived hard carbon is more disordered. 002 Compared with the comparative example 1, they are all increased and the peak is broadened, indicating that the esterification and cross-linking of starch and coal helps to inhibit the dense accumulation of carbon layers and the ordering of microstructure.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a coal-based hard carbon negative electrode material, characterized in that: Includes steps: (I) performing simultaneous purification and pre-oxidation treatment on coal powder and mixed acid in a solvent to obtain modified coal powder, wherein the mixed acid comprises hydrochloric acid, hydrofluoric acid and nitric acid; (II) solid-phase mixing the modified coal powder and starch to obtain a first precursor, wherein the amylose content in the starch is 50% or more, and the mass ratio of the modified coal powder to the starch is 6-9:1-4; (III) sequentially esterifying and pre-carbonizing the first precursor to obtain a second precursor; (IV) Carbonizing the second precursor to obtain a coal-based hard carbon negative electrode material.
2. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: Includes at least one of the following features (i) to (j): (I) Particle size D of the coal powder v 50: 2μm~10μm; (ii) the concentration of the hydrochloric acid is 36wt.% to 38wt.%, the concentration of the hydrofluoric acid is ≥40wt.%, and the concentration of the nitric acid is ≥20wt.%; (iii) the solvent is selected from water, and the water is tap water or purified water; (iv) the mass ratio of the coal powder, the hydrochloric acid, the hydrofluoric acid, the nitric acid and the solvent is 1.0:0.5-1.5:0.1-0.5:0.1-0.5:1.0-5.0; (V) The temperature of the synchronous purification pre-oxidation treatment is 50°C to 90°C and the time is 4h to 24h; (vi) the esterification and the pre-carbonization are carried out in an inert atmosphere, wherein the inert atmosphere is selected from at least one of nitrogen, helium and argon; (VII) The esterification temperature is 150°C to 350°C, the esterification heating rate is 1°C / min to 10°C / min, and the holding time is 1h to 10h; (VIII) The pre-carbonization temperature is 450°C to 900°C, the heating rate is 1°C / min to 10°C / min, and the holding time is 1h to 10h; (ix) the carbonization is carried out in an inert atmosphere, wherein the inert atmosphere is selected from at least one of nitrogen, helium and argon; (J) The carbonization temperature is 1100°C to 1600°C, the heating rate is 1°C / min to 10°C / min, and the insulation time is 1h to 10h.
3. The method for preparing the coal-based hard carbon negative electrode material according to claim 1, characterized in that: The coal powder is obtained by coarsely breaking, drying and pulverizing the raw coal.
4. The method for preparing the coal-based hard carbon negative electrode material according to claim 3, characterized in that: The invention comprises at least one of the following features (i) to (iv): (i) the raw coal is selected from at least one of lignite, sub-bituminous coal, bituminous coal and anthracite; (ii) The particle size D of the raw coal v 100 is 0.1cm~1.0cm; (iii) the raw coal is dried at a temperature of 50°C to 100°C and for a drying time of 12h to 72h; (iv) The raw coal is pulverized in at least one of a jet mill, a roller mill and a mechanical mill.
5. The method for preparing the coal-based hard carbon negative electrode material according to claim 1, characterized in that: After the synchronous purification and pre-oxidation treatment, the purified pre-oxidation material is filtered once, washed with water, filtered twice until the filtrate is neutral, and then dried.
6. The method for preparing the coal-based hard carbon negative electrode material according to claim 5, characterized in that: The method comprises at least one of the following features (1) to (5): (1) The primary filtration and the secondary filtration are each independently selected from negative pressure filtration, positive pressure filtration or centrifugal filtration; (2) The water washing temperature is 20°C to 90°C and the washing time is 4h to 24h; (3) In the water washing, the mass ratio of the purified pre-oxidized material to water is 1:1 to 50; (4) In the water washing, the water is tap water or purified water; (5) The drying temperature is 50° C. to 100° C., and the drying time is 12 h to 72 h.
7. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: After the carbonization, screening and demagnetization are also sequentially included.
8. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The mesh number of the sieve used for the screening is 300-500 meshes.
9. A coal-based hard carbon negative electrode material, characterized in that: The invention is prepared by the method according to any one of claims 1 to 8.
10. A sodium ion battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material is the coal-based hard carbon negative electrode material according to claim 9.
Citation Information
Patent Citations
Coal-based hard carbon as well as preparation method and application thereof
CN118004996A
Cited By
Lignite-based hard carbon negative electrode material, preparation method and application thereof
CN120328524A